PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP BURNOUT DENGAN WORK LIFE BALANCE SEBAGAI VARIABEL MEDIASI PADA PEGAWAI KANTOR WILAYAH DJBC JAWA TIMUR I - Febriana, Ika; Rahayu, Sri; Fitrianty, Rifda (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effects of workload and work environment on burnout, with work-life balance as a mediating variable among employees of customs and excise regional office I of east java. This study employed a quantitative approach using a survey method. The population and sample consisted of 194 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results show that workload has a negative and significant effect on work-life balance, while the work environment has a positive and significant effect on work-life balance. Work-life balance and the work environment have negative and significant effects on burnout, whereas workload has a positive and significant effect on burnout. Work-life balance also provides complementary partial mediation in the effects of workload and the work environment on burnout. The research model explains 65% of the variance in burnout. These findings indicate that controlling workload, creating a supportive work environment, and strengthening work-life balance are essential for reducing employee burnout.